Phosphoinositide signalling system in platelets of schizophrenic patients and the effect of neuroleptic therapy - Rípová, D; Strunecká, A; Platilová, V; Höschl, C (Prostaglandins, leukotrienes, and essential fatty acids, 1999)
Alterations in the phosphoinositide signalling system have been proposed as a possible biological marker of schizophrenia. We studied the levels of inositol 1,4,5-trisphosphate (IP3), cytosolic Ca2+ concentrations ([Ca2+]i), and the incorporation of [32P]-orthophosphate into inositol phospholipids and phosphatidic acid (PA) in blood platelets of neuroleptic-treated schizophrenics in comparison with controls. The [Ca2+]i was significantly higher in platelets of one month neuroleptic-treated patients (155+/-5.8 nM) in comparison with controls (95+/-5.4 nM). Neuroleptic therapy decreased the [Ca2+]i, but even after long-term therapy it remained significantly higher (114+/-5.7 nM) than in controls. Differences were also found in the level of IP3 between controls (30+/-4.0 pmol/10(9) platelets), drug-free schizophrenics (52+/-9.0 pmol/10(9) platelets) and treated patients (50+/-6.0 pmol/10(9) platelets). The increased turnover of PA was observed in platelets of neuroleptic-treated schizophrenic patients. The study suggests that the regulation of calcium homeostasis and pathways involved in the phosphoinositide signalling system are altered in the platelets of schizophrenics. Neuroleptic therapy did not remove the observed changes in [Ca2+]i and IP3 levels.
Keywords: trombocyty; signální transdukce; Schizophrenia; Phosphatidylinositol Phosphates; Time Factors; mladiství; Phosphatidylinositol 4,5-Diphosphate; vápník; Middle Aged; mužské pohlaví; Inositol 1,4,5-Trisphosphate; Signal Transduction; fosfatidylinositol-4,5-difosfát; Adult; Antipsychotic Agents; Phosphatidic Acids; inositol-1,4,5-trisfosfát; Calcium; fosfatidylinositolfosfáty; ženské pohlaví; Humans; časové faktory; fosfatidylinositoly; schizofrenie; antipsychotika; lidé středního věku; kyseliny fosfatidové; radioizotopy fosforu; dospělí; Blood Platelets; Female; Adolescent; Phosphorus Radioisotopes; Phosphatidylinositols; lidé; Male